2013
DOI: 10.1371/journal.pone.0079590
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Pleckstrin Homology Domain from the Ceramide Transfer Protein: Implications for Conformational Change upon Ligand Binding

Abstract: Ceramide transfer protein (CERT) is responsible for the nonvesicular trafficking of ceramide from the endoplasmic reticulum (ER) to the trans Golgi network where it is converted to sphingomyelin (SM). The N-terminal pleckstrin homology (PH) domain is required for Golgi targeting of CERT by recognizing the phosphatidylinositol 4-phosphate (PtdIns(4)P) enriched in the Golgi membrane. We report a crystal structure of the CERT PH domain. This structure contains a sulfate that is hydrogen bonded with residues in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…The three-dimensional structure of the PH domain of CERT has been resolved by NMR and X-ray diffraction analyses, and these structural biological studies have identified the subregions and amino acid residues that are crucial for PI4P-binding activity in the CERT PH domain (14,15). We measured the 2D 1 H-15 N heteronuclear single quantum correlation (HSQC) spectra of uniformly 15 N-labeled CERT derivatives (Fig.…”
Section: Hyperphosphorylation-mimetic Cert Srm Interacts With the Cermentioning
confidence: 99%
See 2 more Smart Citations
“…The three-dimensional structure of the PH domain of CERT has been resolved by NMR and X-ray diffraction analyses, and these structural biological studies have identified the subregions and amino acid residues that are crucial for PI4P-binding activity in the CERT PH domain (14,15). We measured the 2D 1 H-15 N heteronuclear single quantum correlation (HSQC) spectra of uniformly 15 N-labeled CERT derivatives (Fig.…”
Section: Hyperphosphorylation-mimetic Cert Srm Interacts With the Cermentioning
confidence: 99%
“…The signals, which are visible only in PH-SRM(10E), are indicated by obelisks, whereas those invisible in both WT and 10E are denoted with double daggers. The asterisks indicate that 1 H- 15 N correlation signals were severely degenerated. P, proline residues (Pro-78 and Pro-102).…”
Section: Functional Regulation Of Cert Ph By Phosphorylation Of Srm Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the seven PIs in the mammalian cell, the PH domain binds specifically to PI(3,4,5)P 3 , PI(4,5)P 2 , PI(3,4)P 2 (Lemmon 2007; Lemmon 2008; Kutateladze 2010; Moravcevic et al 2012). Binding of PH domains to monophosphorylated PIPs seems to be less selective and have lower affinity than to that of bisphosphorylated PIPs (Yu et al 2004; Lemmon et al 2007; Stahelin et al 2007; Prashek et al 2013) and others may be coincident detectors for PIPs and sphingolipids or bind sphingolipids alone (Gallego et al 2010). The membrane binding of PH domains is initially driven by non-specific electrostatic interactions, which is followed by specific PIP binding to achieve selective targeting and increase the membrane residence time.…”
Section: Phosphoinositide Binding Modulesmentioning
confidence: 99%
“…PH (pleckstrin homology) domains, consisting of about 100–120 amino acid residues, are found in a wide range of proteins involved in intracellular signalling or as constituents of the cytoskeleton [ 1 4 ]. Although their sequences bear very low similarity, all the determined three-dimensional structures have seven β -strands forming two perpendicular anti-parallel-sheets and one C-terminal α -helix [ 5 ]. PH domains bind either plasma-membrane phosphoinositides or cytosolic inositol phosphates with few exceptions.…”
Section: Introductionmentioning
confidence: 99%